2015
DOI: 10.3389/fmats.2015.00014
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conductive Polyaniline-Coated Electrospun Poly(Vinylidene Fluoride) Mats

Abstract: Electrically conductive polyaniline (PANI)-coated electrospun poly(vinylidene fluoride) (PVDF) mats were fabricated through aniline (ANI) oxidative polymerization on electrospun PVDF mats. The effect of polymerization condition on structure and property of PVDF/PANI mats was investigated. The electrical conductivity and PANI content enhanced significantly with increasing ANI concentration due to the formation of a conducting polymer layer that completely coated the PVDF fibers surface.The PANI deposition on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…PANI had two main weight loss steps. The first stage at about 105°C was related to the presence of moisture, and the second one with a weight loss from 277°C up to 390°C was associated to the decomposition of polymer chains . Therefore, it could be concluded that in the NP3 sample, the weight loss below 400°C was related to the degradation of PANI, and at temperatures above 400°C, the observed weight loss could be attributed to the decomposition of both PANI and PA6.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…PANI had two main weight loss steps. The first stage at about 105°C was related to the presence of moisture, and the second one with a weight loss from 277°C up to 390°C was associated to the decomposition of polymer chains . Therefore, it could be concluded that in the NP3 sample, the weight loss below 400°C was related to the degradation of PANI, and at temperatures above 400°C, the observed weight loss could be attributed to the decomposition of both PANI and PA6.…”
Section: Resultsmentioning
confidence: 94%
“…The first stage at about 105°C was related to the presence of moisture, and the second one with a weight loss from 277°C up to 390°C was associated to the decomposition of polymer chains. 13 Therefore, it could be concluded that in the NP3 sample, the weight loss below Abbreviation: PANI, polyaniline.…”
Section: Thermal Gravimetry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating 3% by weight CNTs to PVDF solution increased the tensile modulus and tensile strength by 32 and 28%, respectively . A significant increase in the Young modulus and a decrease in elongation at break are observed with increasing the PANI concentration to PVDF solution . With regards to the effect of LiCl on the β phase formation of PVDF electrospun fibers and its more piezoelectric response, the evaluation of its web modulus is a vital factor.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation procedure for electrospun mats of PVDF/Mt-PPy.DBSA were based on the method described by Merlini et al (2014Merlini et al ( , 2015. Firstly, a determined amount of PVDF was dissolved in DMF by magnetic stirring in a thermostatic bath for 2 h at 70 • C. Once the temperature downs back to 25 • C (room temperature), acetone was added under stirring in order to decrease the viscosity of the solution (proportion of DMF/acetone−3:1 by weight).…”
Section: Preparation Of Electrospun Matsmentioning
confidence: 99%